2006
DOI: 10.1161/01.atv.0000200082.58536.e1
|View full text |Cite
|
Sign up to set email alerts
|

ABCA1 and ABCG1 Synergize to Mediate Cholesterol Export to ApoA-I

Abstract: Objective-To study the acceptor specificity for human ABCG1 (hABCG1)-mediated cholesterol efflux. Methods and Results-Cells overexpressing hABCG1 were created in Chinese Hamster Ovary (CHO-K1) cells and characterized in terms of lipid composition. hABCG1 expressed in these cells formed homodimers and was mostly present intracellularly. Cholesterol efflux from hABCG1 cells to HDL 2 and HDL 3 was increased but not to lipid-free apolipoproteins. A range of phospholipid containing acceptors apart from high-density… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

23
291
1
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 374 publications
(319 citation statements)
references
References 34 publications
(41 reference statements)
23
291
1
4
Order By: Relevance
“…ABCG1 has been identified as the more likely mediator of cholesterol transport to HDL but not to lipid poor apoAI [265]. Gelissen et al [266] showed that a range of phospholipids containing acceptors other than HDL subclasses are efficient in mediating the export of cholesterol via ABCG1. Acceptors for ABCG1-mediated cholesterol transport can be generated from incubation of cells with lipid free apoAI through the action of ABCA1 alone.…”
Section: Abcg1mentioning
confidence: 99%
“…ABCG1 has been identified as the more likely mediator of cholesterol transport to HDL but not to lipid poor apoAI [265]. Gelissen et al [266] showed that a range of phospholipids containing acceptors other than HDL subclasses are efficient in mediating the export of cholesterol via ABCG1. Acceptors for ABCG1-mediated cholesterol transport can be generated from incubation of cells with lipid free apoAI through the action of ABCA1 alone.…”
Section: Abcg1mentioning
confidence: 99%
“…HDL formation, or biogenesis, involves the efflux of phospholipids and free cholesterol by ABCA1 to lipid-free apoA-I in the extracellular space, generating nascent HDL particles (27). After ABCA1 facilitates HDL biogenesis, these nascent HDLs become efficient substrates for further lipidation by other cellular pathways (e.g., ABCG1) and esterification of free cholesterol to cholesteryl esters (CEs) by lecithin-cholesterol acyltransferase (LCAT) (28,29). Esterification via LCAT converts the amphipathic cholesterol molecule at the surface of the particle to a nonpolar compound that partitions into the particle's core (28).…”
Section: Introductionmentioning
confidence: 99%
“…Responsive Elements in Their 3′ UTR. Because SREBP-2 and LXR control antagonistic aspects of cellular sterol homeostasis, we hypothesized that miR-33 might be involved in repression of LXR target genes, such as ABCA1 and ABCG1, which are known to promote the efflux of cholesterol from cells (17)(18)(19)(20)(21)(22)(23)(24)(25). Analysis of the 3′ UTR regions of ABCA1 and ABCG1 identified sequences in both genes that are partially complementary to miR-33 sequences (Fig.…”
mentioning
confidence: 99%